2014
DOI: 10.1111/imj.12541
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of acute inpatient gout diagnoses and management in a tertiary hospital: the determinants and outcome of a rheumatology consultation

Abstract: Among inpatients with acute gout, rheumatology input was more likely to be sought in younger patients with knee joint disease. When rheumatology input occurred, patients were more likely to have a synovial fluid confirmed diagnosis of gout with appropriate acute management and a follow-up plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Studies of hospitalization in gout are few (120 citations resulted from a MEDLINE search on 16 December 2015 using the keywords gout and hospitalization), which demonstrates that this area is understudied. Studies have focused on seasonal variation [ 11 ], quality of care or specific treatment patterns [ 12 15 ], time trends [ 16 ], economic burden [ 16 , 17 ], or comparison of charges in gout versus non-gout population [ 5 , 17 ]. Several knowledge gaps exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of hospitalization in gout are few (120 citations resulted from a MEDLINE search on 16 December 2015 using the keywords gout and hospitalization), which demonstrates that this area is understudied. Studies have focused on seasonal variation [ 11 ], quality of care or specific treatment patterns [ 12 15 ], time trends [ 16 ], economic burden [ 16 , 17 ], or comparison of charges in gout versus non-gout population [ 5 , 17 ]. Several knowledge gaps exist.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, none of the previous studies examined predictors of inpatient utilization or disposition after hospitalization for gout. Most studies except one study [ 16 ] used non-representative samples from tertiary care centers [ 12 15 ] or combined all crystalline diseases [ 12 , 15 , 17 ], which limited the generalizability of findings to general populations with gout.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of admissions with rheumatology input varied widely between studies, from 17% to 76%, averaging 40% across all studies. Rheumatology input was consistently associated with more intra-articular joint aspirations and/or steroid injections [ 26–31 ]. Those receiving rheumatology input were more likely to have had SU levels measured [ 28 , 30 , 31 ] and more likely to have received outpatient rheumatology follow-up [ 26–28 ], relative to patients without rheumatology input.…”
Section: Resultsmentioning
confidence: 99%
“…Rheumatology input was consistently associated with more intra-articular joint aspirations and/or steroid injections [ 26–31 ]. Those receiving rheumatology input were more likely to have had SU levels measured [ 28 , 30 , 31 ] and more likely to have received outpatient rheumatology follow-up [ 26–28 ], relative to patients without rheumatology input. Four studies reported significant associations between rheumatology consultation and increased utilization of ULT [ 25 , 27 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the majority of hospital admissions are preventable (10); in that audits have demonstrated that patients admitted with gout commonly have elevated uric acid, and are not on appropriate urate lowering therapy (18). It has also been shown that inpatient care of people with gout in tertiary settings does not meet international guidelines (10) (19), and the majority of people followed up in specialised gout outpatient clinics do not meet therapeutic targets (10,16). Given the health care costs in Australia are rising at an alarming rate, gout appears to be a condition in which there is an opportunity to impact admission rates through optimising therapy.…”
Section: Discussionmentioning
confidence: 99%